Survey of CAM interest, self-care, and satisfaction with health care for type 2 diabetes at group health cooperative - Bradley Ryan; Sherman Karen J; Catz Sheryl; Calabrese Carlo; Jordan Luesa; Grothaus Lou; Cherkin Dan C (BMC, 2011)
Abstract Background Very little research has explored the factors that influence interest in complementary and alternative medicine (CAM) treatments. We surveyed persons with sub-optimally controlled type 2 diabetes to evaluate potential relationships between interest in complementary and alternative medicine (CAM) treatments, current self-care practices, motivation to improve self-care practices and satisfaction with current health care for diabetes. Methods 321 patients from a large integrated healthcare system with type 2 diabetes, who were not using insulin and had hemoglobin A1c values between 7.5-9.5%, were telephoned between 2009-2010 and asked about their self-care behaviors, motivation to change, satisfaction with current health care and interest in trying naturopathic (ND) care for their diabetes. Responses from patients most interested in trying ND care were compared with those from patients with less interest. Results 219 (68.5%) patients completed the survey. Nearly half (48%) stated they would be very likely to try ND care for their diabetes if covered by their insurance. Interest in trying ND care was not related to patient demographics, health history, clinical status, or self-care behaviors. Patients with greater interest in trying ND care rated their current healthcare as less effective for controlling their blood sugar (mean response 5.9 +/- 1.9 vs. 6.6 +/- 1.5, p = 0.003), and were more determined to succeed in self-care (p = 0.007). Current CAM use for diabetes was also greater in ND interested patients. Conclusions Patients with sub-optimally controlled type 2 diabetes expressed a high level of interest in trying ND care. Those patients with the greatest interest were less satisfied with their diabetes care, more motivated to engage in self-care, and more likely to use other CAM therapies for their diabetes.